E-sports organizations with franchised networks: formalization of technological and economic development based on optimal operation and upgrade of the hardware - Chyzmar Ivan; Чизмар Іван; Csizmár Iván; Hoblyk Vladimir; Гоблик Володимир (Institute of Society Transformation, 2021)
Abstract. The paper focuses on the priority given to the technological and economic development of e-sports organizations with franchised networks. Attention is paid to the specificity of the process of timely upgrading of e-sports hardware, which involves the upgrading and introduction of new, more sophisticated and advanced gaming and other devices, which determines the number of e-sports disciplines and available e-sports events for the е-sports arena. The success of franchising networks depends on the quantity of the c-sports hardware, which should be similar to the hardware used by the main arena in order to ensure the functionality of a well-structured state-of-the-art training process for e-sport athletes.The purpose of the study is to present a basis for the technological and economic development of e-sports organizations with a franchising network within the formalized system in terms of finding optimal solutions to the problem of hardware upgrades. The study presents a model of technological and economic development of all e-sports organizations with franchised networks as а content area, posing the rules of operation, regulating the process of hardware upgrades and focusing on the sustainability of development. Dynamic programming methods based on Bellman’s equations and the formalization of the problem of hardware replacement through graphic notations, cloud computing in the AnyLogic environment are used to identify and illustrate the features of such solutions.The result of the research is a description of technological development of e-sports organizations with a franchise network with the use of a model that approximates the optimal way of operation and upgrade of related hardware. This development illustrates the optimal way of operation and hardware upgrade of Blizzard Arena and Overwatch League, represented by participants from the United States, the United Kingdom, Germany, France, South Korea and Ukraine. The franchised Overwatch League includes the main arena (Blizzard Arena), as well as Florida Mayhem Club (Miami-Orlando, USA), New York Excelsior Club (New York, USA), London Spitfire Club (London, UK), Vault Club 15 (Kyiv, Ukraine), Immortals Club (Los Angeles, USA), NRG E-sports Club (Berlin, Germany), Misfits Club (Seoul, South Korea), PS4 Training Base (Beijing, China) and Xbox One Training Base (Paris, France). According to the obtained data, the formalization of the technological and economic development of Blizzard Arena suggests a solution to the problem of finding an optimal strategy relevant to optimization of hardware up to the moment of its transfer to the franchised network. Such formalization is highly relevant. They rely on the possible state of the system proposed in our research. That system state identifies the functional Bellman equations. Naturally, emerges a possibility to significantly reduce investment in the e-sports environment of the main arena and the franchise while controlling the quality and functionality of e-sports hardware. The organizations’ focus on two-stage upgrades will reduce investment in major hardware. The study illustrates the formalization of the techno-economic development of the Blizzard Arena through a two-stage upgrade of the Aerocool Advanced Technologies franchise (primary franchise – from producer, secondary franchise – from franchise Blizzard Arena operator). Based on the specific features of the Bellman equations, the development of the Blizzard Arena must take into account the model which determines the feasibility of hardware transferring to a franchised network during the third period of operation, where it operated as long as franchisees enter the maximum profit area. When using the Bellman equations, we suggest that the arena focus on the moment when the function values will correspond to the replacement state of the hardware and the franchise member on the stability of the environment. The formalization of the technical development will make it possible to orient the e-sport organizations with franchised networks to search for conditions sufficient for optimal operation and upgrade of their hardware. As a result, there will appear an optimized system with a content area, which will provide a stable environment for e-sports events at the arena and athletes’ training in franchise clubs.
Editorial Board: https://ea21journal.world/index.php/editorial-board/
Contents: https://ea21journal.world/index.php/187_1-2_2021/
Keywords: E-sport; Franchise; Blizzard Arena; Overwatch League; Hardware; Upgrade; Bellman Equations; Graphic Notations; Dynamic Programming